Charms of the Cynical Reason The Trickster's Transformation in Soviet and Post-Soviet Culture - Lipovetsky, Mark (Cultural Revolutions: Russia in the Twentieth Century, 2010)
The impetus for Charms of the Cynical Reason is the phenomenal and little-explored popularity of various tricksters flourishing in official and unofficial Soviet culture, as well as in the post-Soviet era. Mark Lipovetsky interprets this puzzling phenomenon through analysis of the most remarkable and fascinating literary and cinematic images of soviet and post-Soviet tricksters, including such "cultural idioms" as Ostap Bender, Buratino, Vasilii Tyorkin, Stierlitz, and others. Soviet tricksters present survival in a cynical, contradictory, and inadequate world, not as a necessity, but as a field for creativity, play, and freedom. Through an analysis of the representation of tricksters in Soviet and post-Soviet culture, Lipovetsky attempts to draw a virtual map of the soviet and post-Soviet cynical reason: to identify its symbols, discourses, and contradictions, and by these means its historical development from the 1920s to the 2000s.